2004
DOI: 10.1007/s00253-003-1437-x
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous batch cultures of Aspergillus oryzae by elimination of wall growth in the Variomixing bioreactor

Abstract: A novel principle for mixing and aeration in stirred bioreactors, named Variomixing, was developed. Four baffles are rotated intermittently at a rotational speed slower or similar to the speed of a centrally placed axial flow impeller. Rotational speeds of the baffles and impeller of 5-10 and 500-600 rpm, respectively, results in the highly turbulent flow regime characteristic of conventional bioreactors with high mixing and mass transfer capacities. Stagnant zones around crevices and crannies in which wall gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…Carbon-limited chemostat cultures were performed in a Variomixing Bioreactor [ 41 ]. This bioreactor was designed especially for cultivation of filamentous microorganisms, which have a tendency to adhere to and grow on surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon-limited chemostat cultures were performed in a Variomixing Bioreactor [ 41 ]. This bioreactor was designed especially for cultivation of filamentous microorganisms, which have a tendency to adhere to and grow on surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…In the filamentous fungus Aspergillus oryzae, K s for glucose is 30 mM during glucose-limited growth in chemostat culture (Carlsen et al, 1996). In contrast, Larsen et al (2004) reported a K s for glucose of 19 mM during growth of A. oryzae in batch cultures. K s values determined for growth in both batch and chemostat cultures depend on substrate uptake, metabolism and growth.…”
Section: Introductionmentioning
confidence: 93%
“…A stirred tank reactor, the 'Variomixing' bioreactor (Larsen et al, 2004), designed especially for cultivation of filamentous fungi, was used for chemostat cultivation. This bioreactor has unique features, which reduce attachment of biomass to bioreactor surfaces and concomitant wall growth.…”
Section: Methodsmentioning
confidence: 99%
“…Accurate measurements of titrant addition, required to maintain constant pH in bioreactors where cell metabolism causes pH changes, have been used to monitor growth and physiological states of microbial cultures (17–23). Despite its simplicity and general applicability, this inherent information in pH control has not been used to obtain detailed information about the kinetics of growth and metabolism in microbial cultures during biotransformation.…”
Section: Introductionmentioning
confidence: 99%